An Analysis of Students’ Reading Comprehension of English Fable Texts: A Study of Eighth-Grade Students - Hilmiah Lana; Harto S. Malik; Sri Agriyanti Mestari (Universitas Islam Negeri Palopo, 2026)
This study analyzed the reading comprehension ability of eighth-grade students in understanding English fable texts, with particular emphasis on vocabulary mastery and word recognition. Previous studies on narrative text comprehension have generally focused on broader reading skills, while limited research specifically investigates how vocabulary mastery and word recognition influence students’ comprehension of English fable texts in Indonesian EFL contexts. The research employed an explanatory sequential mixed-method design. Quantitative data were obtained through a reading comprehension test consisting of 50 multiple-choice items administered to 73 students at SMP Negeri 3 Telaga, while qualitative data were collected through semi-structured interviews with nine selected students representing different achievement levels. The quantitative findings indicated that students’ overall reading comprehension ability was categorized as low to moderate, with a mean score of 58.4. Approximately 61% of students were classified in the low category, while 39% were categorized as moderate achievers based on predetermined score classifications. The weakest performance was found in plot comprehension, character analysis, and language features. Qualitative findings revealed that limited vocabulary mastery and weak word recognition were the primary factors hindering students’ comprehension, causing difficulties in constructing meaning, identifying story elements, and interpreting implicit information. The study concludes that vocabulary and word recognition play a crucial role in students’ comprehension of English fable texts and should be prioritized in reading instruction at the junior high school level. This study contributes empirical evidence on how vocabulary mastery and word recognition influence students’ comprehension of fable texts in Indonesian EFL contexts.